Profilin-Dependent Nucleation and Assembly of Actin Filaments Controls Cell Elongation in Arabidopsis . Issue 1 (16th November 2015) - Cao, Lingyan; Henty-Ridilla, Jessica L.; Blanchoin, Laurent; Staiger, Christopher J.
Abstract : Analysis of single actin filament dynamics reveals a novel role for profilin and formins in the generation of branched filament networks in living epidermal cells. Abstract: Actin filaments in plant cells are incredibly dynamic; they undergo incessant remodeling and assembly or disassembly within seconds. These dynamic events are choreographed by a plethora of actin-binding proteins, but the exact mechanisms are poorly understood. Here, we dissect the contribution of Arabidopsis ( Arabidopsis thaliana ) PROFILIN1 (PRF1), a conserved actin monomer-binding protein, to actin organization and single filament dynamics during axial cell expansion of living epidermal cells. We found that reduced PRF1 levels enhanced cell and organ growth. Surprisingly, we observed that the overall frequency of nucleation events in prf1 mutants was dramatically decreased and that a subpopulation of actin filaments that assemble at high rates was reduced. To test whether profilin cooperates with plant formin proteins to execute actin nucleation and rapid filament elongation in cells, we used a pharmacological approach. Here, we used Small Molecule Inhibitor of Formin FH2 (SMIFH2), after validating its mode of action on a plant formin in vitro, and observed a reduced nucleation frequency of actin filaments in live cells. Treatment of wild-type epidermal cells with SMIFH2 mimicked the phenotype of prf1 mutants, and the nucleation frequency in prf1-2 mutant was completely insensitive to these treatments. Our data provide compelling evidence that PRF1 coordinates the stochastic dynamic properties of actin filaments by modulating formin-mediated actin nucleation and assembly during plant cell expansion.